The chaotic relationship between oil return, gold, silver and copper returns in TURKEY: Non-Linear ARDL and Augmented Non-linear Granger Causality - Bildirici, Melike; Turkmen, Ceren (ELSEVIER SCIENCE BV, 2015)
The structure of the relationship between oil prices, gold price, silver price and copper price are not only important for economists but also for policymakers since it contributes to the policy debate on the link between variables and co-movement of the variables. In this paper, the relationship between oil prices and the price of gold and silver was analysed by BDS test, non-linear ARDL approach and two non-linear Granger causality methods for 1973: 1 - 2012: 11 period in Turkey. This study complements previous empirical papers. However, it differs from the existing literature with simultaneous use of nonlinear ARDL and two non-linear causality model: Hiemstra and Jones (1994) non-linear causality and augmented granger causality developed by this paper. The main findings of this paper are: (a) the gold price level showed positive asymmetric response to changes in the oil price in the short-and long-run. The gold price probably possesses some market power and it is a means of store of value. Because of the exception of gold, there is a substantial sluggishness in the adaption to changes in demand. In the long run the exception of gold lags and adjustment costs should play a smaller part; b) there is a unique long-term relationship between oil prices and the prices of gold, silver and cooper; and (c) there is a unidirectional Granger causality between oil price and precious metal price.
Keywords: Oil Return; Gold Return; Copper Return; Silver Return; BDS Test; Non-linear ARDL; Hiemstra and Jones non-linear Causality; augmented non-linear causality; FUTURES MARKETS; PRICES; INDEX; SPOT; Business & Economics; Social Sciences - Other Topics